Zirconium(IV) electrochemical behavior in molten LiF-NaF. (1st March 2018) - Quaranta, D.; Massot, L.; Gibilaro, M.; Mendes, E.; Serp, J.; Chamelot, P.
Abstract: Zirconium has a large number of properties that make it very attractive for different applications in several activity fields (nuclear, pyrotechnics, armament …). This article is devoted to the study of zirconium electrochemical behavior and crystallization phenomena on silver electrode in the LiF–NaF eutectic mixture in the 690–900 °C temperature range, using cyclic voltammetry, square wave voltammetry and chronoamperometry. The result showed that Zr(IV) is reduced into Zr in a simple-step exchanging four electrons and that zirconium nucleation is progressive whatever the temperature and the overvoltage. Nuclei growth takes place in all three dimensions and is limited by diffusion of Zr(IV) ions. The influence of overvoltage on the zirconium nucleation rate was also studied.